ANALISIS PENGEMBANGAN EKONOMI KREATIF MELALUI PARIWISATA BERKELANJUTAN: BUKTI EMPIRIS TORAJA UTARA - Irna Yanti; Dediek Tri Kurniawan; Avrilia Jasnur; Winda Rostani (Institut Agama Islam Negeri Palopo, 2024)
This study aims to determine the effect of sharia pawnshop business income on the level of micro-arrum distribution at PT. Indonesian Sharia Pawnshop for the 2012-2022 period. The research methodology used is descriptive quantitative, namely an approach that emphasizes testing theories or hypotheses through measuring research variables in numbers and conducting data analysis. The sample used came from the Annual Report of PT. There were 11 samples from pawnshops from 2012-2022. The type of data in this research is secondary data. The data analysis methods used are descriptive data tests, classical assumption tests, simple linear regression tests on panel data, t tests (partial) coefficient of determination (R²) tests. Based on data analysis, it states that there is no influence of income on microarrum distribution in 2012-2022.